Electronic Funds Transfer (Washington University Law Quarterly, 1977)
One of the most controversial topics in the computer industry concerns the development of electronic funds transfer (EFT) systems. Although banks have employed EFT in interbank transactions for several years, their recent attempts to replace the check with the debit card to settle a depositor's account have created considerable dissention in the financial community.